Kualitas Tidur, Tingkat Stres, Aktivitas Fisik, dan Konsumsi Pangan dengan Status Gizi - Nur Hikmawaty Syarifuddin; Dodik Briawan; Tiurma Sinaga (Sarana Ilmu Indonesia (salnesia), 2022)
Obesity is one of the nutritional problems in Indonesia. Meanwhile, based on data from Basic Health Research in 2018, the prevalence of overweight was 13.6% and obesity was 21,8%. This study aimed to analyze sleep quality, stress, physical activity, and food consumption with nutritional status. A cross-sectional study design was applied with 60 subjects aged 20-30 years old selected by cluster random sampling method. Characteristics of subjects, sleep quality, stress levels, physical activity, and food consumption data were collected through interviews by structured questionnaires and direct measurements. The results showed no significant between age, gender, allowance, food expenditure, physical activity, and food diversity with nutritional status (p>0,05). In contrast, sleep quality and stress levels were significant to nutritional status (p<0,05), and stress level was the risk factor for the obesity incidence, OR= 6,2 [95% CI 1,9-20,3]. Thus, stress levels are a risk factor that affects individual nutritional status.